Pengaruh Brand Equity Kopi Java Preanger Gunung Tilu terhadap Keberlanjutan Bisnis - Shofwan Azhar Solihin; Nur Fathan Tsani (J-Coop : Journal of Co-operative, 2025)
The aim of this study is to investigate the application of brand equity in the Java Preanger Gunung Tilu coffee brand, to assess the business sustainability of the Margamulya Pangalengan Coffee Producer Cooperative, to evaluate how brand equity influences business sustainability, to determine the efforts needed to enhance brand equity, and to investigate the economic benefits received by members of the Margamulya Pangalengan Coffee Producer Cooperative. The method used is a case study with mixed methods data analysis.Based on the research findings, it was observed that among the four brand equity variables—brand awareness, brand associations, perceived quality, and brand loyalty—the variable with the highest value is perceived quality, which has a final score of 115.3, indicating a fairly good criterion. This means that the factor most motivating consumers to purchase Java Preanger Gunung Tilu coffee is their trust in the product and the belief that it offers good quality. Conversely, the variable with the lowest final score is brand awareness, which has a value of 90, indicating that the Java Preanger Gunung Tilu coffee brand is not well recognized by most consumers.The efforts needed include more aggressive promotion, creating or adding unique features to the product, employing a dedicated customer service administrator, and offering special rewards to frequent repeat customers.